A Field Study of Control System “Redesign”: The Impact of Institutional Processes on Strategic Choice* - ABERNETHY, MARGARET A.; CHUA, WAI FONG (Contemporary Accounting Research, 1996)
This paper studies the role of an organization's accounting control system (ACS) as part of an interrelated control “package,” in which other control systems function either as substitutes or complements. Drawing on resource dependence and institutional theories, it argues that this control mix is not only contingent on the organization's technical environment but also on its institutional environment. In addition, the paper draws on empirical evidence to demonstrate how the design of the “package” is actively shaped by the strategic choices of its dominant coalition. The empirics are based on a longitudinal field study of one large, public teaching hospital in Australia that underwent material changes in its governance structure, culture, and accounting control system. Résumé. Les auteurs étudient le rôle du système de contôle comptable d'une organisation, à titre d'élément d'une « famille » de systèmes de contrôle reliés entre eux à l'intérieur de Iaquelle les autres systèmes de contrôle jouent le rôle de substituts ou de compléments. S'inspirant de la théorie de la dépendance des ressources et de la théorie institutionnelle, ils affirment que cette combinaison de systèmes n'est pas seulement tributaire de l'environnement technique de l'organisation, mais de son environnement institutionnel. Ils se fondent, en outre, sur des constatations empiriques pour démontrer comment la structure de la « famille » de systèmes est activement façonnée par les choix stratégiques du groupe dominant. Les données empiriques proviennent d'une étude longitudinale sur le terrain, menée auprès d'un important hôpital public universitaire australien dont la structure de régie, la culture et le système de contrôle comptable ont connu des transformations majeures.